Statistical significance of modal parameters of bridge systems identified from strong motion data. - Arici, Yalin
Modal parameters of structural system have commonly been determined using system identification (SI) methods for damage detection and health monitoring. For determining the deterioration of the integrity of structural systems correctly, modal parameters of a healthy structure have to be obtained with adequate certainty so that these parameters can be used as reliable references for the healthy system to compare with those of the damaged system. In this study, the statistical significance of modal parameters identified using strong motion time histories recorded on two bridge structures is assessed. The confidence intervals of identified modal frequencies and damping ratios are obtained using Monte Carlo simulations and sensitivity analyses in conjunction with eigenrealization algorithm. The dependence of the statistical bounds on modal parameters is examined. The effect of using different number of sensors on the statistical significanceis evaluated using simulated time history data from a validated finite element model of a bridge.
Keywords: Bridges; Confidence intervals; Earthquakes; Eigenrealization algorithm; Sensors; State-space.